Effects of raloxifene and hormone replacement therapy on serum Th2 and Th3 type cytokine concentrations in healthy postmenopausal women: a randomised controlled trial - Kumru, Selahattin; Yildiz, Fahrettin M.; Godekmerdan, Ahmet; Kutlu, Selim; Yilmaz, Bayram; Gurates, Bilgin (Springer Heidelberg, 2008)
Background Since sex hormones are reported to have important roles in the regulation of immune function, this study was designed to investigate the effects hormone replacement therapy (HRT) and raloxifene (RAL) on serum cytokine concentrations in healthy postmenopausal women. Methods Fifty-three healthy postmenopausal women were randomly assigned and treated by RAL (Group I, [RAL 60 mg daily and continuously], n = 16), HRT (Group II, [2 mg estradiol valerat + 2 mg dienogest, continuously] n = 18) or placebo (Group III, n = 19). Two fasting morning blood samples were obtained from each participant before and 3 months after the treatments. Serum concentration of interleukin (IL)-4 (as a Th2 cytokine) and transforming growth factor-beta (TGF-beta)1 (as a Th3 cytokine), were measured by using commercially available enzyme-linked immunosorbent assay kits. Kruskal-Wallis analysis of variance, Mann-Whitney U, and Wilcoxon Signed-Ranks Tests were used as necessary. Results At the beginning of the study, the chronological ages, menopausal ages, years of amenorrhea, weights, body mass indexes, and blood pressures were not significantly different between groups (P < 0.05). RAL treatment caused a significant decrease on serum IL-4 concentration (P < 0.001). Although HRT caused a 14% decrease in serum IL-4 concentration, this decrease was not statistically significant (P > 0.05). Serum TGF-beta 1 concentrations were significantly decreased by HRT when compared to basal value (P < 0.001), and to control (P < 0.05). RAL treatment has no significant effect on serum TGF-beta 1 concentration (P > 0.05). Conclusion It seems that RAL treatment might cause a decrease in serum IL-4 concentration while valerate plus dienogest treatment as HRT seems to cause a Th3 tendency in healthy postmenopausal women.
24th Joint Meeting of the British-Endocrine-Society -- APR 04-06, 2005 -- Harrogate, ENGLAND
Keywords: menopause; HRT; raloxifene; IL-4; TGF-beta 1